The Change in the Religious Life of Caodaism During the Process of Urbanization in Ho Chi Minh City, Viet Nam Today - Bui, Vu Bao Khuyen (PT FORMOSA CENDEKIA GLOBAL, 2025)
Cao Dai is one of the major religions in Vietnam. In the course of urbanization, this religion has undergone fundamental transformations, particularly in large cities such as Ho Chi Minh City. Based on a study of two specific religious temples, Bau Sen Temple and Thai Hoa Temple, this article evaluates the key characteristics of Cao Dai religious practices in the context of current urbanization. It also outlines the extent to which urbanization in Ho Chi Minh City has influenced Cai Dai, focusing on issues related to the organization and management of the temples. The findings reveal that the religious life of Cai Dai in Ho Chi Minh City today is marked by increasing openness and secularization. At the same time, the persistence of traditional religious rituals and the stable number of adherents reflect the enduring sacredness and deep-rooted faith among Cao Dai followers.